Studi Pendahuluan : Peningkatan Kesejahteraan Masyarakat Pesisir Surabaya melalui Inovasi Olah Mangrove sebagai Tanaman Hias - Iska Desmawati; Muhammad Nasrulloh; Suratno Suratno (JURNAL SOSIAL HUMANIORA (JSH), 2019)
Surabaya, one of the big cities in Indonesia which has a large coastal area. This coastal area has a lot of potential for high biodiversity, mainly mangroves. This study aims to know the first study about potential mangroves, media, and design for the new concept from mangrove products. Based on this study, we know that mangroves that have good potential are Rhizophora mucronata, Avicennia marina, and Bruguiera gymnorhiza. The media used for this study are clay, sand, and local moss. Design for this houseplant could be modified from kokedama. The result from this study will continue to the laboratorium and acclimation step and will name it “MangroveBall” as an icon of tourism from the coastal area in Surabaya and increase the local economy for the society